2007
DOI: 10.17221/680-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Lactobacillus rhamnosus VT1 and its effect on the growth of Candida maltosa YP1

Abstract: The combined effect of initial amount of 18 h <i>L. rhamnosus</i> VT1 inoculum and incubation temperature on the growth of <i>Candida maltosa</i> YP1, an oxidative food spoilage yeast strain, was primarily modelled and studied by standard response surface methodology. This study resulted in the following linear regression equations characterising lag time and growth rate of <i>C. maltosa</i> YP1 in milk in competition with the potentially protective lactobacillus strain. Lag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Results indicated that, lactic and acetic acids were the major acids produced by the five strains. Results are in agreement with those reported by (Liptáková et al, 2007 andZalán et al, 2010), who found that lactic and acetic acid are regarded as the main organic acids produced by lactobacilli. Lactobacillus in general and L. acidophilus in especial were the most active in acids production.…”
Section: Hplc Analysis Of Organic Acidssupporting
confidence: 93%
“…Results indicated that, lactic and acetic acids were the major acids produced by the five strains. Results are in agreement with those reported by (Liptáková et al, 2007 andZalán et al, 2010), who found that lactic and acetic acid are regarded as the main organic acids produced by lactobacilli. Lactobacillus in general and L. acidophilus in especial were the most active in acids production.…”
Section: Hplc Analysis Of Organic Acidssupporting
confidence: 93%
“…At 15 °C, specific growth rate of Lb. plantarum was characterized as the same as the specific growth rate of Lactobacillus rhamnosus VT1 evaluated in study Liptáková et al, (2007). At 18 °C, the stationary phase was reached after 6 days of incubation (µ = 0.1082 h -1 ), and the maximal density of Lb.…”
Section: Resultsmentioning
confidence: 99%
“…Liptáková and co-workers [66] focused on the growth of yoghurt contaminant C. maltosa YP1 in milk as influenced with initial different numbers of Lb. rhamnosus VT1 (ranged from 1 to 15% v/v) and temperature.…”
Section: Antimicrobial Compounds Produced By Lactic Acid Bacteriamentioning
confidence: 99%